Alpine Glacier Shrinkage Drives Shift in Dissolved Organic Carbon Export From Quasi‐Chemostasis to Transport Limitation. Issue 15 (12th August 2019) - Boix Canadell, Marta; Escoffier, Nicolas; Ulseth, Amber J.; Lane, Stuart N.; Battin, Tom J.
Abstract: The export of dissolved organic carbon (DOC) from catchments is considered as an important energy flux through streams and a major connection between terrestrial and aquatic systems. However, the impact that predicted hydrological changes due to glacier retreat and reduction in snow cover changes will have on DOC export from high‐mountain streams remains unclear. In this study, we measured daily runoff and DOC yield during 1 year in Alpine streams draining catchments with different levels of glacier coverage. DOC yield showed a varied response to runoff across the catchments and varied seasonally as a function of the degree of glaciation and vegetation cover. Using space‐for‐time substitution, our results indicate that the controls on DOC yield from Alpine catchments change from chemostasis to transport limitation as glaciers shrink. Plain Language Summary: Mountain glaciers are shrinking owing to climate change. Despite this unprecedented environmental change, the consequences for downstream biogeochemistry are poorly understood at present. We measured every 10 min during 1 year the concentration of dissolved organic carbon and discharge in 12 high‐alpine streams under various influences of shrinking glaciers. Our data suggest that the drivers of the export of dissolved organic carbon from the catchments shift from chemostasis to hydrological transport limitation as glaciers shrink. This finding is critical to better understand the carbon balance at catchment scale in the future of mountains without glaciers. Key Point: Drivers of DOC yield shift from chemostasis to transport limitation as mountain glaciers shrink